IMPLEMENTATION OF PUBLIC FINANCE INNOVATION POLICY IN THE REGIONAL GOVERNMENT OF BEKASI DISTRICT - Susanti Hartono, Rina (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45, 2025)
with a more transparent and accountable system, the public and business actors increasingly trust the fiscal policies implemented by the local government. The objective of this research is to examine the implementation process of public financial innovation policies applied by the Bekasi Regency Government and to identify the supporting and inhibiting factors in the execution of these policies. The research method employed is a descriptive qualitative approach. The results of this study indicate that, to enhance the effectiveness of implementing public financial innovation, several strategies can be applied, including improving human resource capacity through intensive training, strengthening information technology infrastructure, and refining regulations to be more adaptive to the development of digital financial systems.